Simplicity and predictability: a phenomenological study of psychological flow in transactional workers - Clapp, Steven R.; Karwowski, Waldemar; Hancock, P. A. (Frontiers in Psychology, 2023)
Psychological flow is a positive experience achieved through a near-balance of task challenge and skill capability, creating a merging of awareness and action and leading to an intrinsically rewarding feeling. Flow has typically been documented in persons who participate in work and leisure activities where they can exercise a large degree of creativity and agency over their actions in pursuit of their goals. The objective of the present study is to explore the lived experiences of flow in workers in roles where creativity and agency are typically not expected. An interpretative phenomenological analysis approach was employed to attain this objective. Semi-structured interviews were conducted with 17 adults whose role is to perform transactional work, which by its nature affords less opportunity for creative execution. Common themes about participants’ flow experiences are documented. Two broad types of flow are described and a connection is made that the present study’s participants achieve one of those flow types while working. Participants’ feelings, preferences, and actions are mapped to the nine conventional dimensions of flow. Specific non-task work system factors are discussed relative to their influence on participants’ attainment of flow. Limitations of the present study and recommended future research are discussed.